Model Prediksi Perubahan Tutupan Lahan Pada Area Kebakaran Lahan Gambut Menggunakan Model Cellular Automata Markov - Awal, Elsa Elvira; Sukaesih Sitanggang, Imas; Syaufina, Lailan (PT. Bangun Harapan Bangsa, 2023)
During 2016 Riau Province experienced 10,676 hectares of forest and land fires on fire, where Rokan Hilir District was the largest area of forest fires that reach 3,416 hectares. The area of peatlands in Indonesia is currently experiencing degradation because of peatland fires that, result land-use, land-use changes, and forestry. The purpose of this study was to create a prediction model of land cover change in land fire areas using the Cellular Automata Markov model. The Markov Cellular Automata model is used to predict changes in land cover because this model is very suitable to be applied in high-detail spatial phenomena. The results of this study indicate that in the 2000-2003 period is used to predict land cover changes in 2006 due to forest the land fire in March 2002. The results show that plantations has the most significant change, namely 25.36% with a Kappa value of 95.74%. The prediction model of the period 2006-2009 is used to predict land cover changes in 2012 due to forest the land fire in July 2007. The results show that swamp shrub experienced a change of 74.94% with a Kappa value of 93.22%. The prediction model of the period 2014-2016 is used to predict land cover changes in 2018 due to forest the land fire in June 2015. The results show that swamp bushland cover class experienced the most significant reform of 55.07% with a Kappa value of 68.59%. The prediction results from the three periods show good and acceptable results, however the area of land cover as the result of prediction model has quite large difference with the actual land cover. Keywords: cellular automata markov, land fires, peatlands, land-use land-use changes and forestry